An in vivo evaluation of the effects of feed restriction regimens on wooden breast using ultrasound images as a predictive tool. Issue 5 (2nd September 2020) - Simões, C. T.; Vieira, S. L.; Stefanello, C.; Kindlein, L.; Ferreira, T.; Favero, A.; Xavier, B.
ABSTRACT: 1. Gradual feed restriction was applied to broilers in order to reduce growth rate and, as a consequence, gradually impacts wooden breast myopathy occurrence. Ultrasound (US) images of breast muscle in live birds were correlated with breast fillets presenting wooden breast characteristics (WB). 2. A total of 1800 Cobb × Cobb 500 slow-feathering male chicks were fed one of the six feed restriction treatments with 12 replicates of 25 birds each, in a completely randomised design. Birds were fed ad libitum or were pair-fed to 50%, 60%, 70%, 80% or 90% of normal ad libitum intakes from 8 to 49 d to provide a gradual reduction in growth rate. Ultrasound images were obtained weekly from all birds and, in parallel, one bird per pen was weekly slaughtered and the major breast muscle was weighed and WB graded as 0 (normal), 1 (mild hardening in the upper), 2 (moderate hardening in the upper and/or lower), 3 (severe hardening) and 4 (severe hardening with haemorrhagic lesions and yellow fluid). Blood was taken for analysis of enzymes related to muscle cell breakdown. 3. Feed restriction applied at 50%, 60%, 70%, 80% and 90% of the ad libitum feed intake (FI) resulted in decreased body weight gain (BWG; P ≤ 0.05). 4. From 21 to 49 d, the increasing feed restriction led to linear increases (P ≤ 0.05) in WB scores, fibre density as well as breast depth and breast echogenicity. Creatine kinase, lactate dehydrogenase and aspartate aminotransferase concentration decreased linearly when broilers were feed restricted (P ≤ 0.05). 5. Wooden breast was positively correlated with echogenicity at 21 d (r = 0.510), 28 (r = 0.531), 35 (r = 0.470), 42 (r = 0.430) and 49 d (r = 0.548) (P ≤ 0.001). The use of breast echogenicity can be an additional tool to early detect alterations related to wooden breast.